A facile method for integrating direct-write devices into three-dimensional printed parts. (1st May 2015) - Chang, Yung-Hang; Wang, Kan; Wu, Changsheng; Chen, Yiwen; Zhang, Chuck; Wang, Ben
Abstract: Integrating direct-write (DW) devices into three-dimensional (3D) printed parts is key to continuing innovation in engineering applications such as smart material systems and structural health monitoring. However, this integration is challenging because: (1) most 3D printing techniques leave rough or porous surfaces if they are untreated; (2) the thermal sintering process required for most conductive inks could degrade the polymeric materials of 3D printed parts; and (3) the extensive pause needed for the DW process during layer-by-layer fabrication may cause weaker interlayer bonding and create structural weak points. These challenges are rather common during the insertion of conductive patterns inside 3D printed structures. As an avoidance tactic, we developed a simple 'print-stick-peel' method to transfer the DW device from the polytetrafluoroethylene or perfluoroalkoxy alkanes film onto any layer of a 3D printed object. This transfer can be achieved using the self-adhesion of 3D printing materials or applying additional adhesive. We demonstrated this method by transferring Aerosol Jet® printed strain sensors into parts fabricated by PolyJet™ printing. This report provides an investigation and discussion on the sensitivity, reliability, and influence embedding the sensor has on mechanical properties.